Peranan Klausul Choice of Law dalam Penyelesaian Sengketa Kontrak Internasional: Perspektif Hukum Perdata Internasional - Anindya Zakiyah; Aulia Indryani; Muhammad Ilham Pratama; Sri Handayani (Majelis: Jurnal Hukum Indonesia, 2025)
In an era of globalization marked by increased cross-border interactions, legal relationships in international contracts have become increasingly complex and demand legal certainty for the parties involved. This study aims to analyze the implementation of choice of law clauses in the settlement of international contract disputes from the perspective of International Civil Law. The method used is normative legal research with a qualitative analytical approach through a review of regulations, doctrines, and relevant legal literature. The results of the study show that choice of law clauses play an important role in providing legal certainty, efficiency in the dispute resolution process, and protection of the interests of the parties. However, its application is still limited by the principle of public policy and mandatory rules in the forum country. Thus, the choice of law clause is an important instrument that reflects the balance between the principle of party autonomy and the principle of state sovereignty in the practice of International Civil Law.